Effect of Field-Trip Teaching Strategy on Students’ Interest and Achievement in Pollution Studies in Akwanga, Nasarawa State - Olayinka, Alaba Florence; Lega, Asoloko Ezekiel; Aliyu, Yusuf Aseneshi ALIYU (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This research explored the impact of the field trip instructional method on the interest and academic performance of secondary school students in the topic of pollution within Akwanga Local Government Area, Nasarawa State, Nigeria. The main objective was to assess whether this experiential learning approach yields better outcomes than traditional classroom teaching. The study was guided by four research questions and tested four corresponding null hypotheses at a 0.05 significance level. A quasi-experimental design, specifically the non-equivalent pre-test and post-test control group model was employed. The sample consisted of 80 Senior Secondary One (SS I) students (45 boys and 35 girls), selected from a total population of 1,320 SS I students across 16 schools in the area. Two intact classes were chosen through a multi-stage sampling procedure and were randomly assigned to either an experimental or control group. Two instruments developed and validated by the researchers were used for data collection: the Pollution Achievement Test (PAT) and the Interest Scale on Pollution (ISP). The PAT had a split-half reliability coefficient of 0.78, while the ISP had a Cronbach Alpha reliability of 0.82. Both groups received instruction on pollution for a period of three weeks. The experimental group was taught using the field trip approach, while the control group received conventional instruction. Descriptive statistics (mean and standard deviation) were used to analyze the research questions, and t-tests were applied to test the hypotheses. Results showed that the field trip strategy significantly enhanced students' interest and academic achievement in pollution. No significant differences were observed between male and female students in terms of interest levels. Specifically, there was a statistically significant difference in achievement scores between students taught using field trips and those taught conventionally: t(78) = 11.83, p< 0.05. However, gender did not significantly influence interest: t(38) = 1.28, p> 0.05. The study recommends the integration of field trips into science and environmental education curricula, improved teacher training in experiential methods, and stronger institutional support to promote active learning.